Nourished Roots: The kitchen as a living ecosystem, reappropriating a barn in the centre of Skeerpoor - Clifford, Kerry (University of the Witwatersrand, Johannesburg, 2024)
In the centre of Skeerpoort, where the archaic Magaliesberg mountains whisper narratives of time and the fertile landscape breathes life into every seed, a barn stands vacant. Built in 1885 it has a long history, having served as a tobacco crop storage facility, a field infirmary during times of conflict, and a community gathering hall. The barn now waits for a new purpose. Nourished Roots revives the structure. Addressing perspectives, processes and the practice of sustainable redevelopment, the thesis places itself in the field of designing for cultures of conversion. Biophilic architectural principles and adaptive reuse merge to create a place of nourishment and rehabilitation of place, people and community. The research reads context through the study of gastronomy as relationship between food and culture. Nourished Roots introduces the process of (food) fermentation to connect land, space and people by drawing parallels between the human metabolism and the ‘gut health’ of a building. The design explores and amplifies the architectural significance of the kitchen as a key element in the process of food preparation, production and consumption as well as gathering space and a living organism in which traditional fermentation processes have both practical and symbolic meaning. The barn and its newly emerging surrounding serve as a rescaled pantry, scullery, kitchen and dining room. Together they function as a ‘living classroom’ for a rather eclectic community with diverse challenges and needs. The extended programme sets a precedent for sustainable agricultural practices, food storage and production as well as offering an alternative way of living, learning and working. Rooted in the local agricultural traditions of Skeerpoort the thesis considers the intervention as an innovative approach to support food security in the area as well as preserving its biodiversity.
A research report submitted in fulfillment of the requirements for the Master of Architecture, In the Faculty of Engineering and the Built Environment , School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; South Africa; Building Ecosystem; Nourishment; Biophilic Architecture; SDG-17: Partnerships for the goals